2017
DOI: 10.1111/jofo.12203
|View full text |Cite
|
Sign up to set email alerts
|

Predators of bird nests in the Neotropics: a review

Abstract: Predation is the main cause of nest failure among birds and, therefore, a strong selective agent. To fully understand patterns of nest predation, determining the identities of nest predators is crucial. Information about nest predators in the Neotropics, however, is largely anecdotal and not easily accessible in the literature. Our objective was to search the literature and compile a list of the known predators of nests in the Neotropics. We identified 256 species belonging to 67 families of birds, reptiles, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(55 citation statements)
references
References 44 publications
2
49
0
4
Order By: Relevance
“…Yet, this might be underestimated because the toucans brought unseen food in the craw. Toucans in general seem to be representative predators of eggs and nestlings (see Menezes & Marini 2017 for review), which would be related to the timing of the toucans' and passerines' breeding season, since young Ramphastids usually eat protein sources during their development even when their diet is mostly frugivorous (Brehm 1969, Remsen et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this might be underestimated because the toucans brought unseen food in the craw. Toucans in general seem to be representative predators of eggs and nestlings (see Menezes & Marini 2017 for review), which would be related to the timing of the toucans' and passerines' breeding season, since young Ramphastids usually eat protein sources during their development even when their diet is mostly frugivorous (Brehm 1969, Remsen et al 1993.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in open habitat types have shown that the densities of many species decrease next to roads (Benítez-López et al, 2010;Clark & Karr, 1979;Fahrig & Rytwinski, 2009;Illner, 1992), which can be a response to noise (Pescador & Peris, 2007). In addition, road avoidance by forest birds and mammals can extend hundreds of meters from busy roads (Benítez-López et al, 2010;Forman & Deblinger, 2000) and bird and mammals species are important nest predators in the neotropics (Menezes & Marini, 2017). Our results, however, suggest an edgeinterior space use gradient by predators that extend at least 25 m into the forest.…”
Section: Discussionmentioning
confidence: 99%
“…In the neotropics, several studies have revealed that capuchins, often considered as the New World counterparts of macaques, are significant bird nest predators (Ferreira et al, ; Rose, , ). After snakes, these platyrrhines are the second most important bird nest predators in Central and South America (Menezes & Marini, ), and stand out as important nest predators among primates. On small islands in Lago Guri (Venezuela), artificial nest predation rates by wedge‐capped capuchins ( Cebus olivaceus ) reached 100% (Terborgh, Lopez, & José, ).…”
Section: Discussionmentioning
confidence: 99%